Wide-temperature high-voltage electrolyte and preparation method and application thereof
By designing a combination of lithium salt, ethylene glycol dibutyl ether and diluent, a wide temperature and high voltage electrolyte is formed, and anion-derived inorganic rich electrode/electrolyte interface is used to solve the cycle life of lithium metal batteries at extreme temperatures. It achieves stable operation and high cycle life from -30℃ to 60℃.
Patent Information
- Application Number
- CN202411103065.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-17
AI Technical Summary
Lithium metal batteries have limited cycle life due to lithium dendrites growth and interface instability under extreme temperature conditions. The existing electrolyte design is mainly aimed at room temperature and cannot operate stably within a wide temperature range, which affects energy density and safety.
A wide temperature high-voltage electrolyte is designed, using a combination of lithium salt, ethylene glycol dibutyl ether and diluent to realize the lithium metal battery in the range of -30℃ to 60℃ through anion-derived inorganic rich electrode/electrolyte interface. The stable operation within the system uses the unique solvation structure of the EG electrolyte and the combination of the diluent TTE to form an anion-dominated solvation structure, which promotes the desolvation and interface stability of lithium ions.
The high cycle life and stability of lithium metal batteries in a wide temperature range are achieved. The capacity retention rate of Li||NCM811 batteries after cycling 230 times at 30℃/4.4V high voltage is 88.1%, and 92.6% at -30℃. And the stable circulation is over 100 times at 60°C, which is significantly better than the commercial electrolyte.
Abstract
Description
Technical Field
[0001] The present application relates to a wide-temperature and high-voltage electrolyte and a preparation method and application thereof, and belongs to the technical field of lithium metal batteries. Background Art
[0002] Lithium metal has the lowest density (0.534 g / cm 3 ), extremely high theoretical specific capacity (3860mAh / g) and the lowest standard reduction potential (-3.045V vs. standard hydrogen electrode), it is a very promising anode material. By matching with a high-voltage cathode, lithium metal batteries (LMBs) using lithium metal as an anode can provide energy density far exceeding that of traditional lithium-ion batteries (~500Wh / kg). In recent years, lithium metal batteries (LMBs) have entered the field of vision of researchers due to their extremely high energy density.
[0003] In lithium metal battery systems, highly active lithium metal anodes will continuously undergo uncontrolled side reactions with electrolytes, leading to the growth of lithium dendrites and the generation of unstable solid electrolyte interfaces (SEI), continuous consumption of electrolytes, and safety hazards. This makes the cycle life of current lithium metal batteries very limited, especially under extreme temperature conditions. These problems become more serious. As a key component in the battery, the properties of the electrolyte have an extremely important impact on the performance of LMBs. However, most of the current lithium metal battery electrolyte improvement strategies only focus on the performance at room temperature, and there are few studies on the design of electrolytes at extreme temperatures. Therefore, it is urgent to research and develop lithium metal batteries that can operate stably in a wide temperature range. The voltage window has a great influence on the operating voltage, energy density, and cycle life of the battery. With the development of science and technology, complex practical application scenarios such as polar regions, deserts, space, and deep seas further require the future new generation of energy storage battery systems to be able to adapt to extreme conditions of high and low temperatures. Summary of the invention
[0004] In order to solve the problems in the prior art that the cycle life of LMBs is seriously weakened due to the dendrite growth and interface instability of lithium metal batteries, and the problem that it becomes more serious under extreme temperature conditions, the present application provides a wide temperature and high pressure electrolyte and its preparation method and application. From the perspective of the molecular structure design of the electrolyte solvent, a wide temperature and high pressure local high concentration electrolyte (abbreviated as "EG electrolyte") is designed. By utilizing the formed anion-derived inorganic-rich electrode / electrolyte interface, the lithium metal battery can be operated stably in a wide temperature range from -30°C to 60°C, and a good cycle life can be achieved in a wide temperature range.
[0005] This application adopts the following technical solutions:
[0006] A wide temperature and high voltage electrolyte comprises: lithium salt, ethylene glycol dibutyl ether and a diluent.
[0007] Optionally, the molar ratio of the lithium salt to ethylene glycol dibutyl ether is 1:1-2.
[0008] Optionally, the molar ratio of the lithium salt to ethylene glycol dibutyl ether is selected from any value of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:2, or any range therebetween.
[0009] Optionally, the molar ratio of the lithium salt to the diluent is 1:2 to 4.5.
[0010] Optionally, the molar ratio of the lithium salt to the diluent is selected from any value of 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, or any range therebetween.
[0011] Optionally, the lithium salt is selected from at least one of lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate), and lithium perchlorate.
[0012] Optionally, the diluent is selected from at least one of 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether, 1,1,1,3,3,3-hexafluoropropane, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, and 2,2,2-trifluoroethyl formate.
[0013] According to another aspect of the present application, a method for preparing the above-mentioned wide temperature and high voltage electrolyte is provided, comprising the following steps:
[0014] The diluent and the ethylene glycol dibutyl ether solution containing lithium salt are mixed evenly and allowed to stand to obtain the wide temperature and high voltage electrolyte.
[0015] The specific mixing process may be adding the diluent into the ethylene glycol dibutyl ether solution containing the lithium salt, or adding the ethylene glycol dibutyl ether solution containing the lithium salt into the diluent.
[0016] Optionally, the standing time is 12 to 24 hours. The purpose of standing is to eliminate the influence of stirring and allow the anions and cations in the electrolyte to diffuse freely to a balanced state.
[0017] According to another aspect of the present application, there is also provided an application of at least one of the above-mentioned wide temperature and high pressure electrolyte and the wide temperature and high pressure electrolyte prepared according to the above-mentioned preparation method in a lithium metal battery, wherein the negative electrode material of the lithium metal battery is lithium metal.
[0018] Optionally, the positive electrode material of the lithium metal battery is selected from at least one of nickel-cobalt-manganese ternary material, lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, and lithium manganese oxide.
[0019] The beneficial effects of this application include:
[0020] In the wide temperature and high-voltage electrolyte provided in the present application, the butyl groups at both ends of EG have a large steric hindrance, which can weaken its solvation effect on lithium ions and form an anion-dominated solvation structure. At the same time, the longer carbon chain also improves the intrinsic oxidative stability of the EG molecule. The addition of the diluent TTE further weakens the interaction between EG-Li+, allowing more anions to enter the solvation sheath, which not only promotes the rapid desolvation of lithium ions at low temperatures, but also forms an anion-derived inorganic-rich electrode / electrolyte interface, achieving stable operation of lithium metal batteries in a wide temperature range from -30°C to 60°C. The Li||NCM811 full battery equipped with this electrolyte can still maintain a capacity retention rate of 88.1% after 230 cycles at a high voltage of 30°C / 4.4V. Even after further increasing the charge cut-off voltage to 4.5V, it can retain 84.0% of the initial capacity after 150 cycles. In addition, its unique solvation structure can achieve Li at low temperatures. + It can achieve rapid desolvation and form an anion-derived interfacial layer on the cathode and anode surfaces, thereby realizing stable cycling of lithium metal batteries in a wide temperature range. The assembled lithium metal full battery with this electrolyte exhibits ultra-high stability with a room temperature capacity retention rate of 82.8% at -30°C and a capacity retention rate of 92.6% after 150 cycles. Even at a high temperature of 60°C, it can still stably cycle for more than 100 cycles, and its performance is far superior to that of commercial electrolytes. DETAILED DESCRIPTION
[0021] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0022] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0023] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.
[0024] The galvanostatic charge-discharge (GCD) test was performed on a Xinwei battery tester using a 2025 button battery. The temperature inside the battery tester was controlled at 30°C. The high temperature test of the battery was performed by placing the battery in a blast drying oven (Tianjin TAISITE Instrument Co.LTD) at a constant temperature of 50°C and 60°C. The low temperature test of the battery was performed by placing the battery in a low temperature constant temperature box (Cangzhou Huayi TestInstrument Co.LTD) at -30°C.
[0025] Examples 1 to 7
[0026] Lithium bis(fluorosulfonyl)imide (LiFSI) was dissolved in ethylene glycol dibutyl ether (EG) according to the amount in Table 1, and after stirring evenly, 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE) was added at different rates, and stirring was continued to make it fully moderated and uniform, and the electrolyte was obtained after standing for more than 12 hours.
[0027] Table 1
[0028] LiFSI dosage EG dosage TTE dosage Example 1 0.003mol(0.5612g) 1mL 1mL Example 2 0.003mol(0.5612g) 1mL 1.4mL Example 3 0.003mol(0.5612g) 1mL 1.75mL Example 4 0.003mol(0.5612g) 1mL 2mL Example 5 0.003mol(0.5612g) 1.2mL 1.4mL Example 6 0.003mol(0.5612g) 1.2mL 1.4mL Example 7 0.003mol(0.5612g) 1.2mL 1.4mL
[0029] Comparative Example 1
[0030] The commercial electrolyte was purchased from Shenzhen Xinzhoubang Technology Co., Ltd.: the volume ratio of its solvent ethylene carbonate EC and ethyl methyl carbonate EMC was 1:1, and the concentration of lithium hexafluorophosphate (LiPF6) in the combined solvent of ethylene carbonate EC and ethyl methyl carbonate EMC was 1 mol / L.
[0031] Comparative Example 2
[0032] 0.01 mol (1.8706 g) of lithium bis(fluorosulfonyl)imide (LiFSI) was dissolved in 1.1 mL of triethylene glycol dimethyl ether (TG) solvent, and after stirring evenly, 3 mL of 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE) diluent was added, and stirring was continued to make it fully mixed, and the mixture was allowed to stand for more than 12 hours to obtain an electrolyte.
[0033] Comparative Example 3
[0034] 0.01 mol (1.87 g) of lithium bis(fluorosulfonyl)imide (LiFSI) was dissolved in 1.35 mL of diethylene glycol dimethyl ether (DG-DME), stirred evenly, and then 5.6 mL of 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE) was added. The mixture was allowed to stand for more than 12 hours to obtain an electrolyte solution, in which the molar ratio of LiFSI, DG-DME and TTE was 1:0.95:3.7.
[0035] Test Example 1
[0036] Battery assembly: The assembly order of 2025 button cells is positive electrode shell, aluminum foil (19 mm), NCM811 positive electrode sheet (diameter 14 mm), electrolyte, diaphragm (diameter 19 mm), lithium metal negative electrode (diameter 15.6 mm), nickel foam (diameter 16 mm), negative electrode shell, and the packaging pressure is 0.7 T to prepare Li||NCM811 battery. The amount of electrolyte added is 100 μL. In addition, since LiFSI will corrode the stainless steel positive electrode shell under high pressure, an aluminum foil is placed between the positive electrode shell and the positive electrode sheet to prevent the positive electrode shell from being corroded.
[0037] Battery performance test: Shenzhen Xinwei battery tester is used to test the discharge capacity and cycle life of lithium metal batteries. The battery is activated with a small current cycle of 0.1C in the first two cycles, and then a long-cycle constant current charge and discharge test is performed with a current of 0.5C. The voltage range is 3.0-4.4V / 4.5V to test the electrochemical performance of Li||NCM811 batteries. Battery testing at high temperature is carried out in Tianjin Tester blast drying oven, with the temperature set to a constant temperature of 50 / 60℃, a charge and discharge rate of 0.5C, and a voltage range of 3.0-4.4V. Low temperature testing is carried out in Cangzhou Huayi low temperature constant temperature box, with a low temperature discharge test rate of 0.1C, a cycle test rate of 0.2C, and a voltage range of 3.0-4.4V.
[0038] In the high temperature performance test of the Li||NCM811 battery, charge and discharge were carried out under the conditions of 50°C, 0.5C and 3.0-4.4V. Taking the electrolyte prepared in Example 3 as a typical example, the battery with the electrolyte prepared in Example 3 of this document can be stably cycled 100 times with a capacity retention rate of 84.0%, while the battery with the commercial electrolyte of Comparative Example 1 failed after only less than 50 cycles. Even under the conditions of 60°C, 0.5C and 3.0-4.4V, the battery with the electrolyte of Example 3 of this document can be stably cycled for more than 100 times with a capacity retention rate of 65.4%. The test results of Examples 1-2 and 3-7 are similar to those of Example 3.
[0039] However, under the conditions of 60°C, 0.5C and 3.0-4.4V, the capacity retention rate of the battery with commercial electrolyte after 100 cycles is only 0.3%, while the capacity retention rates of the battery with electrolyte prepared in Comparative Example 2 and Comparative Example 3 after 100 cycles are 81.2% and 75.4%, respectively. It can be seen that after the electrolyte with ethylene glycol dibutyl ether (EG) as the solvent used in the present application is applied to the battery, the high temperature stability of the battery is slightly lower than that of the battery with electrolytes in Comparative Examples 2 and 3, but far exceeds that of the battery with commercial electrolysis in Comparative Example 1.
[0040] In the low temperature performance test of Li||NCM811 battery, it was first charged to 4.4V at a rate of 0.1C at 30°C, and then transferred to -30°C for discharge at a rate of 0.1C. Taking the electrolyte prepared in Example 3 as a typical example, the battery room temperature discharge capacity retention rate of the electrolyte prepared in Example 3 of this document was 82.8%, while the commercial electrolyte in Comparative Example 1 was only 30.5%. Charge and discharge were performed under the conditions of -30°C, 0.2C and 3.0-4.4V. The battery using the electrolyte in Example 3 of this document can maintain a capacity retention rate of 92.6% after 150 stable cycles. Under the same test conditions, the test results of Examples 1-2 and Examples 3-7 are similar to those of Example 3, while the room temperature discharge capacity retention rates of the batteries using the electrolytes in Comparative Examples 2 and 3 are 40.2% and 52.7%, respectively, and the low temperature performance is significantly lower than the effect of the electrolyte in which ethylene glycol dibutyl ether (EG) is used as a solvent in this application.
[0041] The test results show that the electrolyte using ethylene glycol dibutyl ether (EG) as a solvent is applied to the battery. Its performance under high temperature and high pressure is slightly inferior to that of the electrolyte using triethylene glycol dimethyl ether (TG) solvent and diethylene glycol dimethyl ether (DG) as a solvent, but compared with commercial electrolytes, the electrolyte of this application is still at a relatively high level. In terms of low temperature performance, the electrolyte of this application shows better performance when applied to batteries than triethylene glycol dimethyl ether (TG) solvent and diethylene glycol dimethyl ether (DG). The reason why the electrolyte of the present application achieves better low-temperature performance is that the ethylene glycol dimethyl ether molecule itself has the advantages of a wide liquid phase range, low density and low viscosity, and is a good solvent for a wide temperature electrolyte. The group at the end of the solvent molecule chain is extended from a methyl group to an n-butyl group compared to triethylene glycol dimethyl ether (TG) solvent, diethylene glycol dimethyl ether (DG) and ethylene glycol dimethyl ether (DME). The extension of the solvent molecule carbon chain not only improves the intrinsic oxidative stability of the solvent molecule, but also increases the steric hindrance, weakening its ability to bind to lithium ions, which is beneficial to the construction of anion-rich solvation structure and the rapid desolvation process of lithium ions at low temperatures. The high temperature performance and high pressure stability of triethylene glycol dimethyl ether (TG) solvent and diethylene glycol dimethyl ether (DG) are derived from the strong chelating effect between the multiple oxygen atoms on the molecule and lithium ions. However, at the same time, the viscosity of triethylene glycol dimethyl ether (TG) solvent and diethylene glycol dimethyl ether (DG) is very large and their strong binding ability with lithium ions is not conducive to the desolvation process of lithium ions at low temperatures, so their low temperature performance is poor.
[0042] In summary, the electrolyte using ethylene glycol dibutyl ether (EG) as the solvent used in the present application can achieve more balanced indicators in the battery and has good application prospects in a wide temperature range.
[0043] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A wide temperature and high voltage electrolyte, characterized in that: The wide temperature and high voltage electrolyte comprises: lithium salt, ethylene glycol dibutyl ether, and a diluent.
2. The wide temperature and high pressure electrolyte according to claim 1, characterized in that: The molar ratio of the lithium salt to ethylene glycol dibutyl ether is 1:1-2.
3. The wide temperature and high pressure electrolyte according to claim 1, characterized in that: The molar ratio of the lithium salt to the diluent is 1:2 to 4.
5.
4. The wide temperature and high pressure electrolyte according to claim 1, characterized in that: The lithium salt is selected from at least one of lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate), and lithium perchlorate.
5. The wide temperature and high pressure electrolyte according to claim 1, characterized in that: The diluent is selected from at least one of 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether, 1,1,1,3,3,3-hexafluoropropane, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, and 2,2,2-trifluoroethyl formate.
6. The method for preparing the wide temperature and high pressure electrolyte according to any one of claims 1 to 5, characterized in that: The steps include: The diluent and the ethylene glycol dibutyl ether solution containing lithium salt are mixed evenly and allowed to stand to obtain the wide temperature and high voltage electrolyte.
7. The preparation method according to claim 6, characterized in that: The standing time is 12 to 24 hours.
8. Use of at least one of the wide temperature and high pressure electrolyte according to any one of claims 1 to 5 and the wide temperature and high pressure electrolyte prepared by the preparation method according to any one of claims 6 to 7 in a lithium metal battery, characterized in that: The negative electrode material of the lithium metal battery is lithium metal.
9. The use according to claim 8, characterized in that: The positive electrode material of the lithium metal battery is selected from at least one of nickel-cobalt-manganese ternary material, lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, and lithium manganese oxide.
